The Process of Forming Communicative Competence in Future Educators in the Process of Vocational Training - Kosimov Muzaffar Shahobaliyevich (International Journal on Integrated Education, 2021)
The process of formation of communicative competence in future educators in the process of professional training reveals the conditions of pedagogical conditions